Evaluation of the Effect of Elevation on Terrain-Induced Slugging in a Riser System - Bright Bariakpoa Kinate; Olalekan Kunle Akindele; Emeline Adaoma Temple (Journal of Earth Energy Science, Engineering, and Technology, 2022)
This work investigates the impact of elevation on terrain-induced slugging in a riser system. Fluid compositions were modeled with multiflash and exported to OLGA in a readable PVT Table File. Pipeline materials and properties with geometry of different elevation were modeled in OLGA to develop a flowline model. Two geometries (1 and 2) of different elevations were defined to establish their effect on accumulated liquid volume flow, surge liquid volume, slug length, number of slugs and slug density. The result shows that Geometry 1 with a total elevation(height)of 450 ft has a total liquid volume flow of 10.1058 ft3/s and Geometry 2 with a total elevation(height) of 300 ft has a total liquid volume flow of 0.197822 ft3/s for the same time of 2473.99 seconds. Also, Geometry 1 has a surge liquid volume of 543.4608484 ft3 at a drain rate of 0.20843960 ft3/s and Geometry 2 with a surge liquid volume of 210.7395 ft3 at a drain rate of 0.23892 ft3/s. There was no slug length and number of slugs in pipe of Geometry 1 while Geometry 2 has a slug length of 531.78 ft indicating severe slug in Geometry 2 system of different elevation. The slug density of Geometry 2 system was twice that of Geometry 1. Change in the elevation for the geometries has shown a significant effect on terrain–induced slugging in the pipe-riser system.